2016
DOI: 10.1007/s10943-016-0323-7
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Fasting Effects on Postural Control in the Elderly: A Comparison Between Fallers and Non-fallers

Abstract: Our purpose was to compare the effects of Ramadan fasting on postural control in elderly fallers and non-fallers. The protocol involved twenty-four healthy old volunteer males divided into two groups: fallers (mean age = 75.43 ± 5.26 years, weight = 67.25 ± 5.30 kg and height = 1.65 ± 0.02 m) and non-fallers (mean age = 72.3 ± 6.42 years, weight = 65.5 ± 6.15 kg and height = 1.64 ± 0.03 m). Participants performed a simple reaction time test (SRT) and a postural control protocol on four different occasions: one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…To our knowledge this is the first study assessing intermittent fasting in association with ILEF. Our findings of an increased risk of balance impairment in participants on TRF are in line with previous publications in older adults who practiced Ramadan fasting [29,30]. A study among 15 older men showed that fasting approximately 17 hours per day for four weeks had a detrimental effect on postural balance performance and in simple reaction time [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge this is the first study assessing intermittent fasting in association with ILEF. Our findings of an increased risk of balance impairment in participants on TRF are in line with previous publications in older adults who practiced Ramadan fasting [29,30]. A study among 15 older men showed that fasting approximately 17 hours per day for four weeks had a detrimental effect on postural balance performance and in simple reaction time [29].…”
Section: Discussionsupporting
confidence: 92%
“…Another study compared the effects of Ramadan fasting on postural control between a group of 12 participants with a history of at least two spontaneous and unexpected falls during the previous year and a group of 12 non-fallers. Ramadan fasting had similar adverse effects on in postural control both groups, that could lead to balance dysfunction and mobility limitation in older adults [30]. Despite Ramadan fasting is a common variety of TRF, it is of note that fasting time is approximately 12 hours per day from dawn to sunset [17], which contrast with TRF in our study participants and with usual TRF diets.…”
Section: Discussionmentioning
confidence: 56%
“…Three studies were retrieved through screening of previous systematic reviews. Altogether, there were 19 prospective studies [ 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and 48 retrospective/case-control studies [ 18 , 19 , 21 , 23 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ...…”
Section: Resultsmentioning
confidence: 99%
“…Fasting can adversely affect postural control of elderly people; this is worse in those who are habitual fallers pre-Ramadan [158]. During Ramadan, there is partial sleep deprivation, which can adversely affect cognitive function, attention and memory [159].…”
Section: The Elderlymentioning
confidence: 99%
“…A pre-Ramadan fasting programme consisting of planned changes in mealtimes and altered sleeping habits can help the elderly adapt to the changes during Ramadan. Particular emphasis is to be laid on maintaining sleep duration by going to bed early and on avoiding unaccustomed surfaces and inadequate environments, such as wet surfaces and reduced ambient lighting, to minimize the risk of falling [158]. A review of all medications, including hypoglycaemic agents with varying hypoglycaemic potential, is essential.…”
Section: The Elderlymentioning
confidence: 99%